Diazepam Alters the Ultrastructure of Fetal Atrium in Rat (International Journal of Medical and Surgical Sciences, 2016)
Diazepam (DZ) is a synthetic minor tranquilizer, used in patients with psychological and psychiatric disorders. It is a relaxing sedative, anticonvulsant and antipsychotic. DZ crosses the human placental barrier in mouse. Young women who are addicted to the drug, if they become pregnant and continue to use it, particularly during the first trimester, expose their children to psychomotor disorders. The purpose of this study was to investigate whether DZ administered during pregnancy induces ultrastructural alterations of fetal mouse myocardium. The group (DZ) of pregnant female mice of the CD-1 strain was treated with a single daily dose of 1.0 mg / kg / pc / sc of day 6 to 17 and a group (C) that received saline solution. On day 18 females of both groups were anesthetized, the fetuses were perfused by intracardiac route with 1 % paraformaldehyde and 2.5 % glutaraldehyde, the heart was removed, the atrium was dissected, fixed in 1 % OsO4, it was immersed in epoxy resin. The fine sections were contrasted with uranyl acetate and lead citrate and observed in a transmission electron microscope. In the myocytes of the fetuses of the DZ group, the sarcomers of the compact myocardium were shorter than those of the C group. Areas with disorganized myofibrils were observed. The sarcoplasmic reticulum of some myocytes had distended and fragmented cisterns, altered mitochondria, and abundant polyribosomes were observed. The changes may be due to the effect of DZ on the synthesis of actin and heavy myosin and on cytoplasmic organelles mediated by peripheral benzodiazepine receptors present on the outer membrane of the mitochondria and associated with voltage-dependent calcium channels. Ultrastructural alterations of the atrial myocardium of fetuses of mice exposed to DZ in utero may have postnatal effects.